An Adaptive Control of A Stepper Motor Drive Using a Hysteresis Current Control Approach - Shrashti Sahu; Pawan Pandey (Journal of Power Electronics and Devices, 2022)
Stepper motors are widely used in industrial and consumer applications due to their low cost, great dependability, and capability for open-loop control. Open-loop has a straightforward design, but it has a low step objective, a big torque wave, and low energy productivity. A new sensorless speed control structure based on hysteresis current regulator is proposed in order to work on the exhibition without increasing equipment costs. It does not convert currents between a-b and d-q coordinates using Park and inverse Park transformations, in contrast to the traditional sensorless speed control. The dynamic performance of the hysteresis current controller is excellent. It has been extensively studied and used in inverter fed drives and voltage source inverters. This approach provides quick dynamic performance and incorporates the virtual rectifier stage’s line modulation methodology into the overall modulation. The outcomes of the simulation and experiment show that the suggested plan is efficient and workable. Through experimentation and evaluation of the suggested controller’s speed and position tracking capabilities, MATLAB/Simulink simulation (R2020a) is used to confirm its efficacy.